INVESTIGASI GEJALA HISTERESIS PADA TERMOMETER TAHANAN PLATINA - Erawan, Dede (National Standardization Agency of Indonesia, 2013)
The hysteresis of a platinum resistance thermometer (PRT) affects significantly the uncertainty of temperature measurement by this sensor. This phenomenon is hard to measure at the time whenthe PRT is calibrated so that its contribution to the measurement uncertainty in the calibration is frequently determined in reference to external information or previous measurements.This paper describes measurement of hysteresis on some PRTs in some common measurement spans covering 0ºC to 150ºC, 100ºC to 300ºC and 350ºC to 500ºC. The measurement is based on Zwak’s hypothesis that the largest hysteresis occurs at the middle of the temperature span and the smallest at each end of the increasing and decreasing temperature curves. The magnitude of the hysteresis depends on the width of the temperature span and the PRT hysteresis coefficient.The measurement result shows that the PRT resistance difference at the same temperature obtained when temperature is increasing and decreasing is maximum just at the lowest point of the corresponding span, then gets smaller as the temperature increases, and reaches zero at the highest point. The largest value in the three temperature spans is 0.0044ºC, 0.15ºC and 0.056ºC respectively. Key words: Platinum resistance thermometer, hysteresis, measurement uncertainty.